2012
DOI: 10.1091/mbc.e11-06-0537
|View full text |Cite
|
Sign up to set email alerts
|

Matrix rigidity regulates a switch between TGF-β1–induced apoptosis and epithelial–mesenchymal transition

Abstract: Matrix rigidity regulates a switch between TGF-β1–induced cell functions in two epithelial cell lines. On compliant polyacrylamide gels, TGF-β1 induced apoptosis, whereas on rigid gels, cells underwent an epithelial–mesenchymal transition (EMT). Compliant gels reduced PI3K/Akt activity, which was essential for cell survival and EMT on rigid gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
350
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(369 citation statements)
references
References 77 publications
18
350
1
Order By: Relevance
“…We test the model for varying ECM stiffness (0.1-1000 kPa) and confinement due to channel widths between 20 and 80 mm, emulating several previous experiments (1)(2)(3)(4)9,13). Consistent with the known ability of cells to actively respond to ECM stiffness (3,4,14), our model predicts that cell clusters scatter more readily on stiffer ECMs. Surprisingly, the cells trapped within 2D islands do not undergo scattering (13) as they do inside 3D channels with vertical walls (9).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…We test the model for varying ECM stiffness (0.1-1000 kPa) and confinement due to channel widths between 20 and 80 mm, emulating several previous experiments (1)(2)(3)(4)9,13). Consistent with the known ability of cells to actively respond to ECM stiffness (3,4,14), our model predicts that cell clusters scatter more readily on stiffer ECMs. Surprisingly, the cells trapped within 2D islands do not undergo scattering (13) as they do inside 3D channels with vertical walls (9).…”
Section: Introductionmentioning
confidence: 59%
“…Over the years, numerous experimental studies have revealed new phenotypes of mechanosensitive and ECMdependent cell scattering and EMT (1)(2)(3)(4)9,13,19,31,32). However, a clear conceptual framework of how cellular mechanisms of forces and adhesions physically interact with the ECM and enable EMT was missing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is not mediated by Smad signaling, but by the PI3K/Akt pathway. 133 Matrix stiffness is important in controlling control the strength of AJs in collective migration. 134 The composition of the matrix itself is regulated by the fibroblasts, which can be activated by paracrine factors secreted from the tumor.…”
Section: The Fate Of Cell-cell Adhesion In Tumor Progressionmentioning
confidence: 99%